2011
DOI: 10.1111/j.1440-1681.2011.05537.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia inhibitory factor is expressed in rat gastrocnemius muscle after contusion and increases proliferation of rat L6 myoblasts via c-Myc signalling

Abstract: SUMMARY Leukaemia inhibitory factor (LIF) has been shown to have an important role during muscle regeneration. The regenerative capacity of muscles after contusion injury in LIF-knockout mice is impaired compared with that of wild-type mice.To clarify whether LIF modulates muscle regeneration by regulating myogenic precursor cell activity, we studied LIF expression and myogenic precursor cell activity in gastrocnemius muscles from Wistar rats at various times after contusion injury using immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Having established that Msx1 interacts with G9a, we next asked whether genomic binding by Msx1 is associated with increased levels of H3K9me2 on its repressed target genes in myoblast cells. In particular, we examined the status of H3K9me2 as a consequence of Msx1 expression at several sites on MyoD as well as several other myogenic regulators that are repressed by Msx1 [23] , namely Myf5 , Angpt1 , Myc , Six1, and Snai2 [28] [34] ( Figure 2A and 2B ). Interestingly, we found that binding by Msx1 resulted in increased levels of H3K9me2 on certain but not all of these genomic binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Having established that Msx1 interacts with G9a, we next asked whether genomic binding by Msx1 is associated with increased levels of H3K9me2 on its repressed target genes in myoblast cells. In particular, we examined the status of H3K9me2 as a consequence of Msx1 expression at several sites on MyoD as well as several other myogenic regulators that are repressed by Msx1 [23] , namely Myf5 , Angpt1 , Myc , Six1, and Snai2 [28] [34] ( Figure 2A and 2B ). Interestingly, we found that binding by Msx1 resulted in increased levels of H3K9me2 on certain but not all of these genomic binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in regenerating crush injured muscle found that Lif mRNA was up-regulated within as little as 3 hours after injury and persisted for up to 4 days (Barnard et al, 1994;Kurek et al, 1996). Similarly in a more recent study, Lif mRNA was shown to be up-regulated rapidly and transiently, from 3-12 hours post injury, in rat gastrocnemius muscles following contusion injury (Srikuea et al, 2011). In the present study, Lif mRNA appeared to be up-regulated in two separate phases following notexin injury.…”
Section: Expression Of Lif During Notexin Induced Regeneration Is Assmentioning
confidence: 53%
“…When recombinant LIF was added to myoblast cultures, the number of cells increased more rapidly over time than compared to controls without LIF (Austin et al, 1992;Austin and Burgess, 1991). Whilst some studies have attributed the increased myoblast cell number induced by LIF to an increased rate of mitosis (Bower et al, 1995;Srikuea et al, 2011;Wang et al, 2008), others including us have reported that LIF does not increase the rate of myoblast mitosis under normal proliferative conditions (Alter et al, 2008;Hunt et al, 2010;White et al, 2001).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…IL-15 decreases lipid deposition in preadipocytes and the mass of white adipose tissue (Quinn et al, 2005 ). LIF induces cell proliferation, which is considered to be essential for proper muscle hypertrophy and regeneration (Broholm and Pedersen, 2010 ; Srikuea et al, 2011 ). Considering this, the role of interleukins and other myokines in the beneficial action of exercise in the treatment of metabolic, cardiovascular, lung, and musculoskeletal disorders is widely discussed (Pedersen and Febbraio, 2008 ; Pedersen and Saltin, 2015 ).…”
Section: Introductionmentioning
confidence: 99%